HUBUNGAN IBU NIFAS USIA REMAJA TERHADAP KEJADIAN POSTPARTUM BLUES DI WILAYAH KECAMATAN NALUMASARI JEPARA - Rina Saputri; Widya Mariyana; Rinda Intan Sari (STIKES Telogorejo Semarang, 2024)
The postpartum period is a crisis situation for mothers due to various changes that occur physically, psychologically, and family structures that require an adaptation or adjustment process. From the records of the Jepara District Health Office in 2021, data obtained from 127 of 392 maternity mothers (32.4%) experienced postpartum blues symptoms between the ages of 17-19 years. This study aims to determine the relationship of adolescent postpartum mothers to the incidence of post partum blues in the District of Nalumsari Jepara. This study uses an analytical design with a cross sectional approach. The population in this study were mothers who gave birth to teenagers in July 2022 at the Nalumsari Health Center Jepara with a total of 35 respondents. The sampling technique used was total sampling. The research instrument used the EPDS questionnaire. Data analysis was performed using the Chi-Square statistical test. The results showed that (1) most of the respondents as many as 20 people (57.1%) were in their late teens (16-19). (2) The incidence of Post partum Blues in postpartum mothers who did not experience postpartum blues were 14 people (40%), mild postpartum blues were 9 people (25.7%) and severe postpartum blues were 12 people (34.3%) . (3) the results of the bivariate analysis showed that there was no relationship between postpartum mothers in their teens to the incidence of post partum blues in the District of Nalumsari Jepara (p-value 0.254 > 0.05). This shows that age is not the main factor in the incidence of postpartum blues but is caused by other factors such as support from husbands, parents and physical fatigue. In addition, the level of maturity of a person cannot be determined by age alone. It is expected that mothers who will undergo childbirth will increase their knowledge regarding psychological adaptation during the postpartum period and the factors that influence the incidence of postpartum blues by carrying out activities during antenatal care so that there is preparation to undergo the delivery process until postpartum and take good care of the baby.